Pengaruh Takaran Pupuk Kandang Kotoran Burung Puyuh Terhadap Pertumbuhan dan Hasil Tanaman Sawi Putih (Brassica Juncea L.) / The Effects of Doses Quail Manure on The Growth and Production of White Mustard (Brassica Juncea L.) - Maria Erviana Kusuma (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2012)
White mustard represent the delicious leaf vegetable likely and also many containing vitamin A and vitamin C and also a few/little vitamin B. On that account seen from its vitamin content, hence white mustard represent the leaf vegetable which enough good for our body. The research aimed at knowing the effects of doses from quail manure to growth and production of white mustard crop and to obtain get the doses of quail manure able to give the growth and production of highest white mustard crop. This research represent the field attempt use the Group Random Design with five group as replication accurate by factor doses from quail manure (p) with five level that is 0 t ha-1 (p1), 10 t ha-1 ( p2), 15 t ha-1 ( p3), 20 t ha-1 ( p4) and 25 t ha-1 ( p5). The result of this research indicate that the giving fertilizer of the quail manure 15 t ha-1 give the highest variable to crop length, the giving fertilizer of the quail manure 20 t ha-1 give the highest variable to crop length (10 hst and 17 hst), wide of leaf, dirty weight, clean weight and dry weight.